2022
DOI: 10.1080/08897077.2021.2007512
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Substance use Disorders Receiving Continued Care in Skilled Nursing Facilities following Hospitalization

Abstract: Background: As hospitals in the US face pressures to reduce lengths of stay, healthcare systems are increasingly utilizing skilled nursing facilities (SNFs) to continue treating patients stable enough to leave the hospital, but not to return home. Substance use disorder (SUD) can complicate care of patients transferred to SNFs. The objective of this paper is to understand SNF experiences for this population of patients with comorbid SUD transferred to SNFs and examine care experiences in these facilities. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In fact, we find some evidence that facilities that accept complex patients are in fact more likely to receive critical and often missing information related to patients' behavioral, social, mental, and functional status. This is reassuring from a quality of care perspective, given that hospitals are known to act cautiously with respect to sharing information that could make patients difficult to place 4,26 . As health system leaders and policymakers continue to grapple with how best to strengthen systems of care and improve value across PAC providers (home health, long‐term care hospitals, and intermediate care facilities), further investment in improving transitional care practices for all facilities—with a focus on these social and behavioral information elements—will be increasingly critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we find some evidence that facilities that accept complex patients are in fact more likely to receive critical and often missing information related to patients' behavioral, social, mental, and functional status. This is reassuring from a quality of care perspective, given that hospitals are known to act cautiously with respect to sharing information that could make patients difficult to place 4,26 . As health system leaders and policymakers continue to grapple with how best to strengthen systems of care and improve value across PAC providers (home health, long‐term care hospitals, and intermediate care facilities), further investment in improving transitional care practices for all facilities—with a focus on these social and behavioral information elements—will be increasingly critical.…”
Section: Discussionmentioning
confidence: 99%
“…If the SNF reported accepting patients at least sometimes in two or more of the three focus conditions, we defined them as willing to accept more complex patients after hospital discharge. These conditions—SMI, MAT, and SUD—were identified as challenging to care for in our formative case studies, and in prior literature because they require additional capacity for psychosocial support 23–26 . We opted to compare the acceptance of two to three complex conditions to zero to one because the theoretical and empirical literature on organizational specialization suggests that organizations are more likely to change structures and processes of care only when they can be applied to a broader segment of their patient population 27–29 …”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have shown that healthcare providers' stereotypes of patients with OUD such as their perceived dangerousness can lead to avoidance. 7,[22][23][24] Second, SNFs might not have the resources to invest in programs that patients with OUD require such as recovery-focused programming or social workers who can address negative social determinants. 23,24 Finally, SNFs face challenges in continuing medications for OUD, particularly methadone.…”
Section: Discussionmentioning
confidence: 99%
“…7,[22][23][24] Second, SNFs might not have the resources to invest in programs that patients with OUD require such as recovery-focused programming or social workers who can address negative social determinants. 23,24 Finally, SNFs face challenges in continuing medications for OUD, particularly methadone. Unlike acute care hospitals, SNFs cannot dispense methadone for OUD and must coordinate with opioid treatment programs for delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Despite federal antidiscrimination laws that protect individuals with OUD (unless they are engaged in active substance use) and those who are in treatment or recovery, an emerging literature suggests that individuals with OUD and those who receive medications for OUD (MOUD) are less likely to be placed in SNFs. Staff unpreparedness to care for residents with OUD; negative perceptions about risk to facility, staff, and other residents; lack of resources; and discriminatory admissions practices appear to limit access to SNFs . The existing literature is based on a few states, and, in some instances, emerged from expert opinion, pointing to the need for further empirical investigation in diverse states and more contemporary periods considering the evolving landscape of OUD treatment policies in the US.…”
Section: Introductionmentioning
confidence: 99%